Kaya's escape : a survival story - Shaw, Janet Beeler, 1937- (Pleasant Company, 2002)
In the fall of 1764, after Kaya and her sister are kidnapped from their Nez Perce village by enemy horse raiders, she tries to find a way to escape back home. Includes historical notes on education and learning among the Nez Perce Indians.